2009
DOI: 10.1007/s00011-009-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic protection by glycyrrhizin and inhibition of iNOS expression in concanavalin A-induced liver injury in mice

Abstract: The present study suggests that the prevention by GL of Con A-induced hepatitis is due partly to the modulation of hepatic iNOS induction and of degeneration of hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In the present study, the production of NO and the expression of iNOS in lung tissues increased significantly after LPS administration, which were markedly inhibited by GL pretreatment in a dose-dependent manner. These effects are in agreement with the study, indicating that GL attenuated concanavalin A-induced acute liver injury by reducing the expression of iNOS mRNA and protein [16]. Likewise, in the animal model of acute liver injury induced by carbon tetrachloride, the increase in iNOS protein level was significantly attenuated by GL treatment [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the production of NO and the expression of iNOS in lung tissues increased significantly after LPS administration, which were markedly inhibited by GL pretreatment in a dose-dependent manner. These effects are in agreement with the study, indicating that GL attenuated concanavalin A-induced acute liver injury by reducing the expression of iNOS mRNA and protein [16]. Likewise, in the animal model of acute liver injury induced by carbon tetrachloride, the increase in iNOS protein level was significantly attenuated by GL treatment [19].…”
Section: Discussionsupporting
confidence: 92%
“…It has been attributed to numerous pharmacologic effects like anti-inflammatory, antiviral, anti-tumor, and hepatoprotective activities [14]. It has been shown that GL inhibited the inflammation in mice model of liver injury [15,16]. To date, unfortunately, the protective role of GL in ALI is not well characterized.…”
Section: Introductionmentioning
confidence: 97%
“…Further, HIF-1α upregulates iNOS expression leading to nitric oxide production which is necessary for pro-inflammatory macrophage function 56 . Accordingly, nitric oxide has a well-described role in perpetuating Con-A-induced liver injury 57, 58 . Our data suggests that pharmacologic blockade of C/EBPβ and HIF-1α is protective in Con-A hepatitis and is associated with decreased iNOS expression in various leukocyte subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB is a transcription factor that promotes the expression of pro-inflammatory genes that activate immune responses 46 . The roles of iNOs, PAI-1, and MCP-1 are involved in Con A-mediated hepatitis 4749 . Therefore, the expressions of these inflammatory cytokines in our studies demonstrated that the condition of aging is more susceptible to immunosenescence-mediated inflammatory injury in livers challenged with Con A.…”
Section: Discussionmentioning
confidence: 99%